The Announcement Effect of Equity Private Placement: Evidence from Malaysia - Nordin, Norhafiza; Abdul Manab, Norlida; Zainuddin, Zaemah (Serials Publications Pvt. Ltd, 2017)
This study examines the Malaysian stock market reaction to the announcement of equity private placement made by 127 publicly listed firms for the period from 2013 to 2015. Using standard event study methodology, the results for different event windows show zero announcement effect in response to the announcements.The finding is inconsistent with majority of past studies’ results which indicate positive announcement effect.Thus, it can be concluded that the market is indifferent to the announcement of private placement and both hypotheses cannot be applied to explain the announcement effect of equity private placement in Malaysia.